Synergistic effects of nitrogen metabolites on auxin regulating plant growth and development - Fu, Yu-Fan; Yang, Xin-Yue; Zhang, Zhong-Wei; Yuan, Shu (Frontiers in Plant Science, 2022)
Nitrogen is one of the important nutrients required for plant growth and development. There is increasing evidences that almost all types of nitrogen metabolites affect, at least to some extent, auxin content and/or signaling in plants, which in turn affects seed germination, plant root elongation, gravitropism, leaf expansion and floral transition. This opinion focuses on the roles of nitrogen metabolites, NO3−, NH4+, tryptophan and NO and their synergistic effects with auxin on plant growth and development. Nitrate reductase (NR) converts nitrate into nitrite, and was roughly positive-correlated with the root auxin level, suggesting a crosstalk between nitrate signaling and auxin signaling. Abscisic Acid Responsive Element Binding Factor 3 (AFB3) and Tryptophan Aminotransferase of Arabidopsis 1 (TAA1) are also the key enzymes involved in nitrogen metabolite-regulated auxin biosynthesis. Recent advances in the crosstalk among NO3−, NH4+, tryptophan and NO in regulation to NR, AFB3 and TAA1 are also summarized.